2017
DOI: 10.1002/mame.201700024
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cross‐Linked Electrospun Polyvinyl Alcohol Membranes and Their Potential Applications

Abstract: range of applications. [1][2][3] It is a suitable polymer for the novice electrospinning to produce nanofibers as it is inexpensive, nontoxic, and water soluble. However, due to its water solubility, it needs to be stabilized, for example, by cross-linking to enable its practical application in waterbased environments to be realized. There are several studies demonstrating cross-linking of electrospun PVA membranes and their water stabilization. [4][5][6][7][8][9] Three major cross-linking methods have been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 23 publications
3
50
0
Order By: Relevance
“…NCFs with 15% loading of nanoclay reached an acceptable swelling level of 52%, which is much lower than those reported for PVA/chitosan/HNTs NCFs crosslinked with gluteraldehyde which exhibited 137% swelling with 5% loading of nanoclay [ 81 ]. Different research groups have reported the preparation of crosslinked PVA films using citric acid with concentrations in the range of 10–50 wt.% [ 82 , 83 , 84 , 85 ]. However, Brick et al reported that PVA films crosslinked with 40 wt.% citric acid, cured at 130 °C for 40 min, showed brittle behavior due to the excessive crosslinking density without any observed plastic deformation [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…NCFs with 15% loading of nanoclay reached an acceptable swelling level of 52%, which is much lower than those reported for PVA/chitosan/HNTs NCFs crosslinked with gluteraldehyde which exhibited 137% swelling with 5% loading of nanoclay [ 81 ]. Different research groups have reported the preparation of crosslinked PVA films using citric acid with concentrations in the range of 10–50 wt.% [ 82 , 83 , 84 , 85 ]. However, Brick et al reported that PVA films crosslinked with 40 wt.% citric acid, cured at 130 °C for 40 min, showed brittle behavior due to the excessive crosslinking density without any observed plastic deformation [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of a chemical crosslinking agent allows the formation of three-dimensional structure which can prevent the PVA dissolution in water, due to the further decrease in the hydroxyl groups [41]. Among the various crosslinking chemical agents, maleic anhydride (MA) is one of the most effective crosslinking agents to be used for the enhancement of the electrospun PVA stability [42,43]. The objectives of this work were: (1) to produce composite membranes from PVA and CNFs by electrospinning technique; (2) to compare the individual and combined additivation effects of the polymeric matrix with a natural filler (CNFs) and a chemical crosslinking agent (MA) in the solution parameters (viscosity and electrical conductivity);…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out that the formation of crosslinked fibers is demanding, as most electrospinning processes usually require the polymer to be dissolved. Alternative strategies are based on the electrospinning of a linear polymer which is crosslinked during or after the fiber formation process …”
Section: Introductionmentioning
confidence: 99%
“…Alternative strategies are based on the electrospinning of a linear polymer which is crosslinked during or after the fiber formation process. [31][32][33][34][35][36][37] There are only few reports on the formation of fibers by electrospinning polymeric nanoparticles followed by the removal of the spin polymer. [26,[38][39][40][41][42][43][44] Stoiljkovic et al [26] were the first to produce stable polymer nanoparticle fibers consisting of polystyrene (PS) by electrospinning PS latex particles from an aqueous dispersion.…”
Section: Introductionmentioning
confidence: 99%